Perkawinan di bawah Tangan Menurut Hukum Islam dan Undang-Undang No. 1 Tahun 2019 (Study Kasus Dusun II Desa Sungai Ular) - Deni Aprilia (Journal Smart Law, 2022)
This thesis discusses underhand marriage. This aims to analyze the factors that cause someone to carry out an underhand marriage and what impacts are felt by people who do not register marriages. In terms of its arrangement, this research uses qualitative methods, qualitative research is a data analysis in which the author describes the data obtained from the results of the study. The results of this study indicate that there are not many people in Dusun II Sungai Ular Village who carry out underhand marriages who do not register their marriages. However, more people who do not live in Hamlet II of Sungai Ular Village are carrying out underhand marriages. Due to various factors, one of which is the certificate of divorce from a previous marriage that has not been completed. Whereas in Law Number 1 of 1974 concerning marriage as amended by Law Number 16 of 2019 it is stated that: "Every marriage is recorded according to the applicable laws and regulations", and has also been regulated in the Compilation of Islamic Law regarding marriage registration. expresses several legal lines as follows: "In order to ensure orderliness of marriage for the Islamic community, every marriage must be recorded", it is clear that the law requires registration of marriages, but there are still many people who do not register and think that marriage registration is not important, it only takes time and effort. not a small fee. Â